Transplantation Immunology
DOI: 10.1385/1-59745-049-9:331
|View full text |Cite
|
Sign up to set email alerts
|

Organ Preservation

Abstract: The success of organ transplantation is critically dependent on the quality of the donor organ. Donor organ quality, in turn, is determined by a variety of factors including donor age and preexisting disease, the mechanism of brain death, donor management prior to organ procurement, the duration of hypothermic storage, and the circumstances of reperfusion. It has been recognized for some time that both the short- and long-term outcomes after cadaveric organ transplantation are significantly inferior to those o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 0 publications
0
53
0
1
Order By: Relevance
“…The former distinguishes itself by its relatively high glucose content (214 mmol/l) and is best suited for lung preservation (Hicks et al, 2006), while the latter is characterized by three impermeants (lactobionate, raffinose, and hydroxyethyl starch) and is well-matched for kidney, liver and pancreas preservation (Hicks et al, 2006). Both solutions are unsuitable for the preservation of muscle and extremities (Tsuchida et al, 2001(Tsuchida et al, , 2003.…”
Section: Cell Free Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The former distinguishes itself by its relatively high glucose content (214 mmol/l) and is best suited for lung preservation (Hicks et al, 2006), while the latter is characterized by three impermeants (lactobionate, raffinose, and hydroxyethyl starch) and is well-matched for kidney, liver and pancreas preservation (Hicks et al, 2006). Both solutions are unsuitable for the preservation of muscle and extremities (Tsuchida et al, 2001(Tsuchida et al, , 2003.…”
Section: Cell Free Solutionsmentioning
confidence: 99%
“…Hydroxyethyl starch (Handrigan et al, 2005;Matharu et al, 2008) and cellulose (Hänsch et al, 1996;Moore et al, 2001;Bae et al, 2004;Ewoldt et al, 2004;Hernández et al, 2004Hernández et al, , 2009 have also both been shown to alter inflammatory responses due to their different effects on neutrophils. While glucose is also able to support the maintenance of oncotic pressure (Hicks et al, 2006), it supports the specimen's metabolism and survival. Glycolysis represents the main energy source for living tissue, ensures ATP production under anaerobic and aerobic conditions (Silbernagl and Despopoulos, 2012) and is consumed by specimens in perfusion experiments.…”
Section: Cell Free Solutionsmentioning
confidence: 99%
“…However, because cooling to about 4°C does not completely arrest metabolic processes in the cells, utilization of a correct washout technique and an appropriate preservation solution is crucial for organ viability. Complete washout of all blood cells from the vascular space ensures uniform distribution of the preservative throughout micro vessels resulting in decreased immune reaction and formation of oxygen-free radicals upon reperfusion [27].…”
Section: Organ Carementioning
confidence: 99%
“…The evergrowing demand for transplantation, however, is not matched by the supply of suitable donor hearts (2). This supply shortage is due to the relatively small pool of organ donors, compounded by the fact that a significant number of hearts are not recovered and transplanted, often due to organ dysfunction and an unwillingness to use suboptimal donors (3)(4)(5)(6). Additionally, the transplant waiting list mortality rate has been reported to be as high as 17-22% per year (1,3).…”
Section: Introductionmentioning
confidence: 99%
“…The success of transplantation is critically dependant upon the quality of the donor organ, which is significantly influenced by the process of donor brain death (6)(7)(8)(9)(10)(11). Reported consequences of brain death include hemodynamic instability and donor organ dysfunction (7,9,10,12,13), rejection of organs for transplantation, and an overall increase in posttransplant complications (6,7,13,14).…”
Section: Introductionmentioning
confidence: 99%